RETRACTED: Gastroprotective Studies of Raw and Processed African Pear (Dacryodes edulis var. edulis) on Experimentally Induced Gastric Mucosa Ulcer in Wistar Rats - Inyang, Aniekeme Ndisa; Mgbang, John Edward; Asanga, Edet Effiong; Takim, Burch Ndifon; Etim, Ubong Gabriel; Ottoho, Ediye; Agiang, Margaret Akpana (African Journal of Biochemistry and Molecular Biology Research, 2025)
Gastric ulcer is one of the most prevalent gastroduodenal disorders worldwide, and this study evaluated the gastroprotective effects of raw and processed African pear (Dacryodes edulis var. edulis) in Wistar rats. A total of 84 rats were divided into two experimental phases of 42 animals each, with six rats randomly assigned to seven groups per phase. The groups included a control and diets supplemented with 15% raw, 30% raw, 15% roasted, 30% roasted, 15% boiled, and 30% boiled samples, administered alongside standard rat chow. Food and water were provided ad libitum for 28 days. At the end of the feeding period, gastric acid, pH, mucus, pepsin secretion, and ulcer indices were measured using standard procedures. Results showed significantly (p < 0.05) higher mean mucus output and gastric pH in the group fed 30% raw samples compared with the control and other groups. Ulcer scores were significantly higher (p < 0.05) in the 15% roasted group, while pepsin secretion was significantly increased (p < 0.05) in the 30% boiled group relative to the control and other groups. Basal gastric acid secretion was significantly elevated (p < 0.05) in groups fed processed samples compared with both raw-fed and control groups. The study concludes that processed African pear contains phytochemicals that stimulate gastric secretion, likely through H₂-histaminergic receptor pathways. Therefore, consumption of processed African pear pulp should be approached with caution, while intake of raw pulp is preferable for gastric health.